Open-Ended Transmission Coaxial Probes for Sarcopenia Assessment - Paul Meaney; Shireen D. Geimer; Roberta M. diFlorio-Alexander; Robin Augustine; Timothy Raynolds (Sensors, 2022)
We developed a handheld, side-by-side transmission-based probe for interrogating tissue to diagnose sarcopenia—a condition largely characterized by muscle loss and replacement by fat. While commercial microwave reflection-based probes exist, they can only be used in a lab for a variety of applications. The penetration depth of these probes is only in the order of 0.3 mm, which does not even traverse the skin layer, and minor motion of the coaxial feedlines can completely dismantle the calibration. Our device builds primarily on the transmission-based concept that allows for substantially greater signal penetration depth operating over a very broad bandwidth. Additional features were integrated to further improve the penetration, optimize the geometry for a more focused planar excitation, and juxtapose the coaxial apertures for more controlled interrogation. The larger coaxial apertures further increased the penetration depth while retaining the broadband performance. Three-dimensional printing technology made it possible for the apertures to be compressed into ellipses for interrogation in a near-planar geometry. Finally, fixed side-by-side positioning provided repeatable and reliable performance. The probes were also not susceptible to multipath signal corruption due to the close proximity of the transmitting and receiving apertures. The new concept worked from 100 MHz to over 8 GHz and could sense property changes as deep as 2–3 cm. While the signal changes due to deeper feature aberrations were more subtle than for signals emanating from the skin and subcutaneous fat layers, the large property contrast between muscle and fat is a sarcopenic indication that helps to distinguish even the deepest objects. This device has the potential to provide needed specificity information about the relevant underlying tissue.